Is regulation essential to stock market development? Going public in London and Berlin, 1900-1913 - Carsten Burhop; David Chambers; Brian Cheffins (Max Planck Institute for Research on Collective Goods, 2011)
This study of initial public offerings (IPOs) carried out on the Berlin and London stock exchanges between 1900 and 1913 casts doubt on the received law and finance wisdom that legally mandated investor protection is pivotal to the development of capital markets. IPOs that resulted in official quotations on the London Stock Exchange performed as well as Berlin IPOs despite the Berlin market being more extensively regulated than the laissez faire London market. Moreover, the IPO failure rate on these two stock markets was lower than it was with better regulated US IPOs later in the 20th century.
Keywords: G32; K22; N23; G18; G38; G14; G24; 330; regulation; financial history; law and finance; initial public offering; investor protection; Wertpapieremission; Börsenregulierung; Börsenrecht; Wertpapierbörse; Geschichte; Deutschland (bis 1945); Großbritannien